Using alternative waste coir fibres as a reinforcement in cement-fibre composites. (20th January 2020) - Kochova, K.; Gauvin, F.; Schollbach, K.; Brouwers, H.J.H.
Highlights: Coir fibres can be a good replacement of wood fibres. Pre-treatment affect the physical properties and the composition of fibres. Pull-out test shows a good bonding between cement and pre-treated fibres. Mechanical and physical properties of coir boards are close to WWCB. Abstract: Wood-wood cement boards (WWCB) have been extensively used as ceiling tiles or insulating walls thanks to their good thermal and acoustic properties. Nowadays, the trend is to use sustainable materials like waste fibres. These waste fibres are widely available at a low cost and despite their good properties, are usually landfilled or incinerated. Among them, coir fibres, extracted from the husk of the coconut, are a good candidate to replace conventional fibres in composite materials. However, preliminary results have shown that despite their good physical properties and great cement compatibility, coir fibres cement boards have poor mechanical performances. This is mainly due to the poor interface between the cement and the fibre, leading to a very week fibre/matrix load transfer. The objective of the present study is to produce coir fibres cement boards having the required mechanical properties in order to be used as insulated interior wall or ceiling panels. First, the interfacial properties between the fibres and the cement will be investigated and improved by modifying the surface of the fibres thanks to chemical pre-treatments. Then, the process and design of cement boards will be studied in order to optimize the process, improving the overall properties of the boards. Finally, the mechanical and physical properties of these boards will be measured and compared to conventional WWCB.